Disability and other identities?—how do they intersect? - Wickenden, Mary (Frontiers in Rehabilitation Sciences, 2023)
This paper addresses intersectionality and disability in global contexts. Disability as a category of identity is often omitted in rhetoric about intersectionality, which usually considers race and gender, with some consideration of other identities. However, disability like other identities is socially constructed, and liable to misrepresentation and is often siloed from other issues and experiences. Someone identifying as disabled may not be recognised by those around them as having other identities too. In discussions about intersectionality, a simplistic ‘additive’ approach is common, while the shifting complexities and interactions between people’s multiple identities are not considered with nuance. Disabled people may pragmatically adopt a kind of ‘strategic essentialism’. This allows them to claim a disabled identity and a specific dialogic space in order to gain recognition and perhaps access to support and services. However, they may prefer not to be classified in this dichotomised way because this ignores other aspects of them. Often an impairment is only of importance to the extent that it means that the person needs some reasonable adjustments in order to participate on equal basis with others. Arguably the SDGs and other global guidelines and treaties do not address disability as a significant identity sufficiently, nor recognise it as an important aspect of many people in combination with their other identities, rather than a stand-alone feature of them. When analysing the types of disadvantages that people experience, a broader more flexible approach is needed which recognises the ways in which different identities combine and influence people’s experiences.